Designing Smart and Resilient Cities for a Post-Pandemic World : Metropandemic Revolution. - Larsson, Anthony. (Routledge Advances in Regional Economics, Science and Policy Series, 2022)
Through a series of investigative studies, this book critically discusses and compares different cases, innovations and approaches as to how cities can utilise nascent and future digital technology and new strategies in order to build stronger resilience to better tackle comparable large-scale pandemics and future disruptions.